The Role of Human Resources in Human Capital Management - Dharma Diani, Rinny; Hamida, Hamida; Ketut R Sudiarditha, I (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
This article discusses the important role of human resources (HR) in Human Capital Management (HCM) with a theoretical basis from various experts, as well as global case studies that illustrate the implementation of the role of HR in HCM. Based on the theory outlined in